CHANGES IN PHYSICO-CHEMICAL CHARACTERISTICS OF HUMAN LOW DENSITY LIPOPROTEIN NANO-PARTICLES BY ELECTROMAGNETIC FIELD EXPOSURE - ABDI, Soheila; DORRANIAN, Davoud; NADERI, Gholam Ali; EMAMI RAZAVI, Amirnader (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Studies on the effects of electromagnetic field (EMF) exposure on cardiovascular function have provided some evidence of a possible action. Low density lipoprotein (LDL) modifications appear as an early step in the promotion and progression of atherosclerosis, the most causes of death in cardiovascular disease (CVD) patients. This study aimed to evaluate the effects of extremely low frequency (ELF) of electromagnetic fields on LDL physico-chemical modifications. LDL was separated by sequential ultracentrifugation and its susceptibility to oxidation was evaluated by continuous monitoring of conjugated dienes formation, using a spectrophotometer. LDL size and zeta potential is determined by zetasizer instrument. The results indicated that moderate ELF-EMFs of 2-4 mT can induce the susceptibility of LDL to oxidation and aggregation. Weak ELF-EMFs of 0.125-0.5 mT caused a decrease in LDL zeta potential in a time and dose dependent manner while in moderate ELF-EMFs of 1-4 mT LDL zeta potential was started to increase after an initial decrease at the first hour of exposure. LDL oxidation and aggregation are two important modifications of LDL, involved in the promotion and progression of atherosclerosis. On the other hand, alteration of the LDL surface charge can interfere with the metabolism of LDL and its interaction with other molecules. Therefore, with regard to the atherogenic effects of ELF-EMFs on LDL, it can be considered as a risk factor in atherosclerosis.